Good governance in international sport organizations: an analysis of the 35 Olympic sport governing bodies - Geeraert, A.; Alm, J.; Groll, M. (International Journal of Sport Policy and Politics, 2014)
In this article, structural issues with regard to the quality of the self-governance of the 35 Olympic sport governing bodies (SGBs) are analysed. First, this article presents empirical evidence on the lack of accountability arrangements in SGBs. In particular, the watchdog function of their member organizations is severely undermined by the general absence of objective criteria and transparency in the distribution of funding to members. With regard to checks and balances, arguably the most topical issue is the complete lack of independent ethics committees. Second, our survey demonstrates that most SGBs have institutionalized athlete participation. However, in the overwhelming majority of the organizations, they have not been granted a share of formal decision-making power. Third, with regard to executive body members, there is the rather anachronistic dominance of the European continent and also the preponderance of male officials. In addition, the general lack of term limits poses serious threats with regard to the concentration of power, which is evidenced for instance by the overall number of years SGB presidents are in office. The empirical evidence clearly supports the recent calls for improved governance in sport, according to which SGBs need to agree upon, and act in accordance with, a set of well-defined criteria of good governance. Only then will the self-governance of sport be credible and the privileged autonomy of these organizations justifiable.